Dampak Stres Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada Bank Nagari Cabang Utama Sumatera Barat - Gia Sonya; Zusmawati Zusmawati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
One way to improve employee performance is to pay attention to the level of stress they experience. In addition to stress, workload is also a factor that affects employee performance. Although a heavy workload can spur increased performance, if the workload is too excessive, performance can actually decline. The purpose of this study was to determine the effect of work stress and workload on employee performance at Bank Nagari, Main Branch of West Sumatra. Through the questionnaire method with samples using purposive sampling techniques, there were 163 respondents who were used as samples in this study. In the hypothesis testing that has been carried out, it can be concluded that work stress has a positive and significant effect on employee performance at Bank Nagari, Main Branch of West Sumatra and workload has a positive and significant effect on employee performance at Bank Nagari, Main Branch of West Sumatra.